Management of the leaf roller complex on rice Oryza Sativa L - Lekha M (Department of Agricultural Entomology, College of Agriculture, 2003)
The magnitude and intensity of leaf roller complex and natural enemies at different growth stages of the rice crop were assessed in a survey conducted during Mundakan season of 2002, adopting random sampling technique in Kalliyoor panchayat of Thiruvananthapuram district. The survey revealed the occurrence of two different species of leaf roller viz., Cnaphalocrocis medinalis (Guenee) and Marasmia patnafis (Bradley). The distribution pattern of these two species in the n ce ecosystem varied. C. medinalis had a population peak during the vegetative stage and showed a gradual decline as the crop growth progressed, whereas, M. patnalis had a population peak during the early reproductive stage compared to vegetative and late reproductive stage. The natural enemies recorded from the rice ecosystem incl ude three parasites and ten predators. The distribution of natural enemies in the rice ecosystem revealed that the population of parasites and predators showed a gradual increase from vegetative to reproductive phase. From the field experiment, it was evident that the synthetic insecticides alone and botanicals + half dose synthetic insecticides were efficient in suppressing the pbpulation of rice leaf roller. The treatments with botanicals alone did not show any significant reduction in the population of leaf roller compared to control. G. tr iangulifer, a specific larval parasite of rice leaf roller, was unaffected by the botanicals, synthetic insecticides and their combinations at 30 OAT. In the case of X flavolineata and Cot esia sp., only an initial suppression was noticed in insecticide included treatments. Later it was found to be safe. All these treatments were found to be relatively safe to predatory beetles. But Agriocnemis sp., spiders, predatory bugs and